Sistem Pemasaran Jeruk Siam Gunuang Omeh dengan Pendekatan Structure, Conduct, Performance (SCP) di Kabupaten Lima Puluh Kota - Putri, Mega Amelia; Nefri, John; Dini, Rahma (Department of Agribusiness, Halu Oleo University, 2021)
Gunuang Omeh sub-district is the center of jeruk siam production because it has superior ranges of citrus based on the Mandate of the Minister of Agriculture in 2008. This location has the most extensive variety of farmers, particularly 70.5% (987 farmers). Presently, the asking price of oranges from this location is 69.23% higher than rivals from outside the area. The role of various other marketing establishments is fairly more leading in determining prices than farmers. This research aims to analyze the marketing of Jeruk Siam Gunuang Omeh with a Structure, Conduct, and Performance (SCP) approach. This research was conducted in Kenagarian Koto Tinggi in August 2019 and January 2020. The information used was secondary data and primary. Farmers were selected through purposive sampling and snowball sampling for a middleman. Information processing in this study used qualitative and quantitative detailed evaluation. Based upon the assessment of the market structure, jeruk siam marketing tends to lead to an oligopsony market framework. Going by market habits, there are four marketing channels and marketing functions performed by marketing establishments, mainly the exchange function, physical facility function, and function. On the other hand, market performance evaluation shows that the share of prices received by farmers (farmer's share) is relatively high (>40%). This is because of the lack of various other marketing establishments that execute the processing of jeruk siam. There's no considerable increase in item included worth between marketing firms.